(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
Art and notaries: a not unusual combination which reveals interesting and original facets if projected within a legal-historical perspective. Given this perspective, the present study aims at setting a possible method of investigation and some options of implementation of it. In particular, it suggests using the ‘artwork’ and the complex process that involves it, from commissioning to circulation, as a hermeneutic device and thematic fil rouge, useful for investigating, through archival documents of the modern age, the role of the notary. The notary who, by his legal instruments, acts as a ’mediator’ between wills, languages, generations, and as an active protagonist of a dense network of social, economic and cultural links.